RETRACTED: The Influence of Intrinsic Motivation, Organizational Culture, and Work Discipline on the Performance of Employees in Jakarta BKN Personnel Bureau - Andrew Lanjza Aghiesta; Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This research aims to analyze how much influence intrinsic motivation, organizational culture and work discipline have on the performance of BKN Jakarta personnel bureau employees. Data management uses validity and reliability tests as well as multiple linear regression and multiple correlation using the SPSS 17.0 program. The results of the analysis of multiple linear regression calculations obtained the equation Y = 4.905 + 0.460 X1 + 0.175 X2 + 0.218 X3. This shows that intrinsic motivation (X1), organizational culture (X2), and work discipline (X3) have a positive effect on employee performance (Y). The coefficient of determination (R square) value is 53.3%, this shows that the variables of intrinsic motivation, organizational culture and work discipline contribute 53.3% to the performance of BKN Jakarta personnel bureau employees, while the remaining 46.7% is influenced by variables others not analyzed in this study. The magnitude of this influence shows that intrinsic motivation, organizational culture and work discipline are important elements in improving the performance of BKN Jakarta personnel bureau employees. Keywords: Intrinsic motivation, organizational culture, work discipline, employee performance, Jakarta BKN Personnel Bureau